2011
DOI: 10.1111/j.1365-2885.2010.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a novel amoxicillin/colistin suspension after intramuscular administration in pigs

Abstract: An amoxicillin (AMO) or colistin (COS) oil suspension was developed and corresponding pharmacokinetics studies were conducted in pigs after i.m. injection. The combination product is a white- to cream-colored oil suspension which is easy to be re-dispersed. Settling volume ratio, syringeability and flowability of the product is well consistent with the technical standards set by the Ministry of Agriculture of People's Republic of China. Two studies were conducted to investigate the pharmacokinetics of the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Unlike for human medicine, only a few studies have been conducted in pigs to evaluate the PK of colistin following oral (Guyonnet et al, 2010; Rhouma et al, 2015, 2016b) or intramuscular (IM) administration (Lin et al, 2005; Tang et al, 2009; He et al, 2011; Table 1 ). These studies were performed using CS, since this is the only form of colistin approved in swine medicine, and were conducted in healthy pigs.…”
Section: Pharmacokinetics and Pharmacodynamics (Pk And Pd) Of Colistimentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike for human medicine, only a few studies have been conducted in pigs to evaluate the PK of colistin following oral (Guyonnet et al, 2010; Rhouma et al, 2015, 2016b) or intramuscular (IM) administration (Lin et al, 2005; Tang et al, 2009; He et al, 2011; Table 1 ). These studies were performed using CS, since this is the only form of colistin approved in swine medicine, and were conducted in healthy pigs.…”
Section: Pharmacokinetics and Pharmacodynamics (Pk And Pd) Of Colistimentioning
confidence: 99%
“…However, there are some commercial formulations where CS is associated with others antimicrobial agents, mostly with β-lactam antibiotics (He et al, 2011) such as ampicillin or amoxicillin ( Table 3 ). In fact, it has been shown that the combination of amoxicillin with colistin has a synergy and additive affect in vitro against pathogenic E. coli of avian origin, without antagonism between the two antibiotics (Hamouda et al, 2011).…”
Section: Clinical Use and Indications Of Colistin In Pig Productionmentioning
confidence: 99%
“…In the meantime, it has the advantage of sustained‐release so that prolongs the action time of the drug and reduces the frequency of drug delivery, determining the feasibility of the dosage form in the veterinary clinic. Amoxicillin and ceftiofur hydrochloride oil suspension are typical representations of it (He et al, ; Hibbard et al, ; Tang et al, ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, AMO monotherapy has proven to be less effective in recent times due to the wide-spread occurrence of multi-drug resistant (MDR) bacteria [4, 5]. Antibiotic combination therapy is a far more effective approach for combating MDR pathogens and preventing the emergence of resistance commonly seen with monotherapy [4, 6]. A very effective therapeutic approach is to combine antibiotics with different modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…A very effective therapeutic approach is to combine antibiotics with different modes of action. For example, it has demonstrated that the combination AMO (a cell wall synthesis inhibitor) with antibiotics that act on different cellular targets such as gentamicin [4], colistin [6] and ceftriaxone [7], has been shown to have a marked synergistic effect. Intuitively, we took the novel approach to combine AMO with apramycin (APR), an aminoglycoside which displays a unique bicyclic sugar moiety and a 4-monosubstituted 2-deoxystreptamine ring [8].…”
Section: Introductionmentioning
confidence: 99%